Juvenile Apprehension and Prosecution Process of Indonesia and Philippines: A Comparative Study - Villarico, Johndex; Ika Dewi Sartika Saimima; Hipolito B. Quillip Jr (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2024)
This study aims to compare find out the similarities and differences of the Juvenile Apprehension Prosecution Process of the Philippines and Indonesia. The researchers utilized the descriptive comparative analysis in conducting this study. This research is conducted using secondary data by utilizing the Republic Act 9344 of the Philippines and the Law No. 11 of 2012 of Indonesia as sources. The researcher has the following criteria in comparing if there are provisions under the Republic Act 9344 of the Philippines and the Law No.11 of 2012 of Indonesia that provides for the (a) Apprehension Process (b) Prosecution Process and (c) Ensuring the Confidentiality of the Information Regarding the CICL. The researchers found out that (1) there two (2) similar and (4) different provisions that pertains to the Apprehension Process (2) there are (1) similar and (3) different provisions that pertains to Prosecution Process and (3) that the Republic Act 9344 and Law No. 11 of 2012 have similar provisions that pertains to Ensuring the Confidentiality of the Information Regarding CICL.